Analysis of maternal mortality at a government teaching hospital GMKMCH, Salem, Tamil Nadu, India: a retrospective study - G., Sridevi; L., Shanmugavadivu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Mother is the pillar of the family. Maternal death is a great loss to the baby, family, society and country. Pregnancy although being considered as a physiological state carries risk of serious maternal morbidity and mortality . This is due to various complications that may occur during pregnancy, labour or thereafter. Maternal mortality ratio is a very sensitive index that reflects the quality of healthcare provided by the community to the women population. Methods: A retrospective study of 204 maternal deaths over a period of 56 months from July 2013-february 2018. Demographic data were collected from maternal death review form and records. Data studied and analyzed. Results: During the study period, there were 33968 deliveries and 204 maternal deaths with a MMR of 600.5/1,00,000 live births. Eclampsia was the leading direct cause of death. Anemia was the leading indirect cause of death. Most of the women died within 24 hours of admission suggesting that majority of patients reached the tertiary care hospital quite late. Majority of deaths occurred in the age group of 20-30 years and in postpartum period. Conclusions: Most maternal deaths are preventable by optimal utilization of existing MCH facilities, identifying the bottleneck in health delivery system, early identification of high-risk pregnancy and therein timely referral to tertiary care centre.